2013
DOI: 10.1093/her/cyt076
|View full text |Cite
|
Sign up to set email alerts
|

Formative research on HAPA model determinants for fruit and vegetable intake: target beliefs for audiences at different stages of change

Abstract: Theoretically driven health communications are needed to promote fruit and vegetable intake among people at different stages of change. The Health Action Process Approach, a clearly speci-15 fied model and good predictor of fruit and vegetable intake, was used as a framework to guide a formative research for the development of health messages targeting individuals at either a nonintentional or intentional stage of change. A 20 mixed-method approach was used, combining eight focus groups (n ¼ 45) and a question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…It established that the majority of the target audience was at the pre-contemplation stage of change, which was different to other studies where participants were classified into various stages [65]. In contrast to developed countries where processed foods form the bulk of diet, the formative research confirmed that Indians have preference for home cooked food which is consumed by all family members.…”
Section: Discussionmentioning
confidence: 69%
“…It established that the majority of the target audience was at the pre-contemplation stage of change, which was different to other studies where participants were classified into various stages [65]. In contrast to developed countries where processed foods form the bulk of diet, the formative research confirmed that Indians have preference for home cooked food which is consumed by all family members.…”
Section: Discussionmentioning
confidence: 69%
“…The HAPA as stage model is an interesting template for the theory-based development of dietary health messages that can be adapted to persons at different stages of the behavior change process [38] and was successfully applied in several nutrition behavior change interventions, e.g. [39][40][41].…”
Section: Theory Guidance For Intervention Developmentmentioning
confidence: 99%
“…This shall boost self-efficacy and thereby help to overcome barriers and to achieve target behavior [34,41]. Visual feedback through progress bars were used to replace possible missing intrinsic motivation for behavior change [32].…”
Section: Final Intervention: the C2go Appmentioning
confidence: 99%
“…As it becomes increasingly acknowledged that awareness and sensitization campaigns alone are often not enough to effectively change eating habits, many scholars are in favour of more focused interventions to change such habits (e.g., Godinho, Alvarez, & Lima, 2013;Schwarzer, 2008;Silva, Marques, & Teixeira, 2014;Verplanken & Wood, 2006). In fact, the outline provided on several variables relevant to meat consumption and substitution indicates that there are key issues at distinct levels which are linked to food choice and behaviour (Figure 3).…”
Section: Conclusion: Calling For An Integrated Approach To Food Behamentioning
confidence: 99%
“…For instance, the HAPA model distinguishes between a motivational phase, which leads to forming a behavioural intention, and a volitional phase, which leads to translating the intention into action. Individuals will firstly need to be motivated to change, and only then they should benefit from acquiring and employing a set of skills to implement the desired change (Godinho et al, 2013;Schwarzer, 2008).…”
Section: Conclusion: Calling For An Integrated Approach To Food Behamentioning
confidence: 99%